Anti-Inflammatory Profile of Jungia sellowii Less. by Downregulation of Proinflammatory Mediators and Inhibition of NF-κB and p38 Pathways - Geison Vicente; Yeo Jim Kinoshita Moon; Daniela Weingärtner Rosa; Luíse Azevedo Lima; Najla Adel Saleh; Julia Salvan da Rosa; Tânia Beatriz Creczynski-Pasa; Maique Weber Biavatti; Eduardo Monguilhott Dalmarco; Tânia Silvia Fröde (Hindawi Limited, 2020)
Jungia sellowii Less. (Asteraceae) is a native plant found in Southeast Brazil used traditionally to treat inflammatory diseases. This study was conducted (1) to investigate the toxicity of the crude extract (CE) and (2) to investigate the mechanism of the anti-inflammatory action of J. sellowii L. roots. The potential acute toxicity of CE was performed by administration of only different doses of CE (500, 1,000, and 2,000 i.p.) on mice for 14 days. The anti-inflammatory effect was evaluated using carrageenan-induced acute pleural cavity inflammation in a mouse model, evaluated through the following inflammatory variables: leukocyte, protein concentrations of the exudate, myeloperoxidase (MPO), adenosine deaminase (ADA), nitric oxide metabolites (NOx), and proinflammatory cytokine (tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), interleukin- (IL-) 6, and IL-12) levels in mouse pleural fluid leakage. The p65 protein phosphorylation of nuclear factor NF-kappa B (p65 NF-κB) and p38 mitogen-activated protein kinase (p38 MAPK) phosphorylation were analyzed in lung tissue. Our results demonstrated that the administration of CE up to 2,000 mg/kg did not present a toxic effect. In addition, the pretreatment of mice with CE; its derived fractions (aqueous fraction (AqF), butanol fraction (BuOHF), and ethyl acetate fraction (EtOAcF)); and isolated compounds (curcuhydroquinone O-β-glucose (CUR) and α and β piptizol (Pip)) reduced the following inflammatory variables: neutrophils, protein concentrations of the exudate, MPO, ADA, NOx, and proinflammatory cytokine (TNF-α, IFN-γ, IL-6, and IL-12) levels in mouse pleural fluid leakage. The compounds CUR and Pip also decreased the p65 protein phosphorylation of NF-kappa B and p38 (MAPK) in lung tissue. J. sellowii L. has important anti-inflammatory activity with potential applications in drug development against inflammatory disorders. These effects found can be attributed to the ability of the new isolated compounds CUR and Pip to suppress p65 NF-κB and p-p38 MAPK pathways.